Kepemimpinan Perempuan Berkaca Dari Tokoh Ester Dalam Menjawab Tantangan Gereja Masa Kini - Olifia Christin Lalujan; Yanto Paulus Hermanto (Sekolah Tinggi Teologi Sriwijaya, 2025)
This study aims to explore the relevance of female leadership in the contemporary church through a critical reflection on the figure of Esther using a narrative-feminist hermeneutical approach. Contemporary challenges such as gender inequality within church structures, leadership stagnation, and the need for a contextual leadership model drive this research to address the existing research gap studies on Esther have predominantly focused on the aspect of divine providence, not yet on a strategic and transformative female leadership model for the modern church, particularly in the Indonesian context. This research employs a qualitative approach with a literature review method, integrating the analysis of the Book of Esther through the lens of narrative-feminist hermeneutics with contemporary leadership theories (transformational, servant leadership, and feminist leadership theory). The results indicate that Esther's leadership offers a resilient, contextual, and solidarity-based model a leadership paradigm that works within the system while transforming it from within, emphasizing strategic agency, collaboration, and contextual courage. The contribution of this study lies in its hermeneutical enrichment, which opens space for the empowerment of female church leadership through theological legitimacy from the Old Testament narrative. Thus, the contemporary church needs to reflect on Esther's leadership model to face challenges more effectively and inclusively.